Determinants of Regional Financial Independence: A Study of Local Taxes, Balancing Funds and Capital Expenditure in East Java (2020-2023) - Ayuningtyas, Radina; Nuha, Gardina Aulin; Zulkarnaeni, Achmad Syahfrudin (Universitas Sultan Ageng Tirtayasa, 2025)
Regional financial independence serves as a crucial indicator for evaluating the capacity of a region of a local government to finance spending needs without high dependence on the central government. This research seeks to examine the impact of local taxes, balance funds, and capital expenditures on regional financial independence in local governments of East Java during the 2020-2023 period. The research employs a descriptive quantitative methodology, utilizing a panel data regression approach. The data for this analysis was sourced from the financial statements of local governments, as published by the Supreme Audit Agency (BPK) of the Republic of Indonesia. The findings reveal that local taxes have a positive and significant effect on regional financial independence, while the balance fund demonstrates a negative and significant impact. Furthermore, capital expenditure does not appear to significantly influence regional financial independence. These findings suggest that higher local tax revenues can enhance a region's financial independence, while depending on balanced funds tends to hinder it. Therefore, local governments need to optimize local tax revenues and improve efficiency in the allocation of capital expenditures in order to strengthen fiscal independence.